2017
DOI: 10.1590/0001-3765201720160668
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect of quinoline derivatives containing or not selenium: Relationship with antinociceptive action quinolines are antioxidant and antinociceptive

Abstract: The present study investigated the antioxidant effect of a new class of quinoline derivatives (a-d) on assays in vitro. Lipid peroxidation, thiol peroxidase-like and free radical scavenging activities were determined to evaluate antioxidant activity of compounds. Thiol oxidase-like and δ-aminolevulinate dehydratase activities were performed as a toxicological parameter. A second objective of this study was to evaluate the in vivo antinociceptive effect of the compound with better antioxidant effect and without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…The findings revealed a strong anti-tumour effect against EAC cells by the inducement of antioxidant activities. Moreover, our outcomes agree with Wilhelm et al, 28 who announced that the presenting of an electron withdrawing group into the aromatic ring of the quinoline system affects the antioxidant effect of quinoline derivatives. Removing the single electron characteristic that is responsible for radical reactivity could diminish non-reactive species.…”
Section: Discussionsupporting
confidence: 92%
“…The findings revealed a strong anti-tumour effect against EAC cells by the inducement of antioxidant activities. Moreover, our outcomes agree with Wilhelm et al, 28 who announced that the presenting of an electron withdrawing group into the aromatic ring of the quinoline system affects the antioxidant effect of quinoline derivatives. Removing the single electron characteristic that is responsible for radical reactivity could diminish non-reactive species.…”
Section: Discussionsupporting
confidence: 92%
“…Quinoline pharmacophore has a diverse variety of pharmacological activities, which include anti-tubercular (Fan et al ., 2018a), anti-bacterial (Zhang et al ., 2018), anti-protozoan (Fan et al ., 2018b), anti-fungal (Musiol et al ., 2006), anti-oxidant (Wilhelm et al ., 2017), anti-proliferative (Zhang et al ., 2017), anti-tumour (Sharma et al ., 2013), anti-inflammatory (Upadhyay et al ., 2018), anti-hypertensive (Muruganantham et al ., 2004) and anti-HIV effects (Luo et al ., 2010). Moreover, quinolines can be used for treatment of lupus (Bengtsson et al ., 2012) and neurodegenerative diseases (Wang et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…SAR studies revealed that compound containing aromatic nitrogen can form a free radical and hence results in good antioxidant activity. The compound 101 showed the maximum antioxidant activity value with 63% in 100 μM concentrations in the TBARS assay (Wilhelm et al, 2017). Firoz et al explored the novel quinolone derivatives and reported that compound 102 , was the most potent one as on 16th day the percentage wound contraction was 94% as compared to the 87%, 84.5% contraction of standard povidone‐iodine and control, respectively.…”
Section: Biological Activitiesmentioning
confidence: 99%